Structure and physicochemical properties for modified starch-based nanoparticle from different maize varieties. (June 2017) - Ye, Fan; Miao, Ming; Lu, Keyu; Jiang, Bo; Li, Xingfeng; Cui, Steve W.
Abstract: The molecular structure and physicochemical characteristions of different modified starch-based nanoparticle from maize varieties (octenylsuccinylation treated soluble starch nanoparticle, OS-SSNP, and acid treated insoluble starch nanoparticle, A-ISNP) were investigated. Compared to A-ISNP, OS-SSNP had small-sized particles with spherical shape. FT-IR analysis showed the similar characteristic absorption bands, except small new peaks after chemical treatment. OS-SSNP suspension was stable with a unimodal distribution regardless of pH used, whereas wider distribution peaks were observed for A-ISNP with the increase of pH. Moreover, OS-SSNP formed a homogenous transparent solution exhibiting better stability than A-ISNP, especially under acidic conditions. OS-SSNP was an effective particle emulsifier for long-term stability of emulsion. The rheological measurements showed the Newtonian flow behavior for OS-SSNP solution and the pseudoplastic behavior for A-ISNP, respectively. Results suggested that it was possible to employ OS-SSNP to produce Pickering-type emulsions with improved properties. Graphical abstract: Highlights: Structure and physicochemical properties for different modified starch-based nanoparticles were investigated. OS-SSNP had small-sized particles with spherical shape compared to A-ISNP. OS-SSNP formed a homogenous transparent solution exhibiting better stability than A-ISNP. OS-SSNP was an effective particle emulsifier for Pickering-type emulsions.